Dampak Program Usaha Agribisnis Perdesaan (PUAP) Terhadap Tingkat Pendapatan Petani Studi Kasus pada Gabungan Kelompok Tani Sejahtera Bersama di Desa Lingga Tiga Kecamatan Bilah Hulu Kabupaten Labuhanbatu - Martia Ritonga (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2020)
This study aims to: 1. Identifying the success of the PUAP program in Lingga Tiga Village, Bilah Hulu District. 2. Identifying the constraints and obstacles encountered in the implementation of the PUAP program. 3. Analyzing the amount of farmers' income after participating in PUAP compared to the income of farmers before joining PUAP. The study population was all agribusiness farmers who received PUAP funding assistance. Samples were taken as many as 80 random farmers to answer the problem of this study used descriptive analysis as well as statistical analysis with t test with the help of the SPSS program. The results of this study indicate that the success rate of the PUAP program in Gapoktan Sejahtera Bersama is high. The success rate is immediately up to 53%, seen from the Model Summary table. This shows that the income after the data is higher than the income before. The average income of agribusiness actors after participating in PUAP is Rp. 1.572,25 per month is greater than the income of agribusiness players before joining PUAP, which amounted to Rp. 816,00 per month. And can be seen in the Paired Samples Test Table is the main table of output that shows the results of the tests carried out. This can be seen from the significance value (2-tailed) in the table. The significance value (2-tailed) in this case sample is 0,000 (p <0.05). So that the results of income before and after having experienced a significant change (meaning). Based on descriptive statistics before income and after income proved after income is higher. In the implementation of the PUAP program in the Gapoktan Sejahtera Bersama Lingga Tiga Village, no significant obstacles were found.